2017
DOI: 10.3766/jaaa.15139
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Characteristics of Stroke Patients: Prevalence and Characteristics of Hearing Impairment and Auditory Processing Disorders in Stroke Patients

Abstract: Background: Stroke survivors may suffer from a range of hearing impairments that may restrict their participation in postacute rehabilitation programs. Hearing impairment may have a significant impact on listening, linguistic skills, and overall communication of the affected stroke patient. However, no studies sought to systematically characterize auditory function of stroke patients in detail, to establish the different types of hearing impairments in this cohort of patients. Such information would be clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…It must also be considered that visual hemispatial neglect is not necessarily associated with auditory neglect, and the two conditions might not be associated [ 11 ]. Therefore, it would be useful to conduct an audiometric and audiological examination in post-stroke and post-hydrocephalus patients to identify hearing impairment and to define a more accurate diagnosis leading to an appropriate intervention plan [ 12 ]. In addition to the possible link between balance and hearing recovery, early auditory stimulation after a stroke should be recommended to improve neural organization in the recovering brain [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…It must also be considered that visual hemispatial neglect is not necessarily associated with auditory neglect, and the two conditions might not be associated [ 11 ]. Therefore, it would be useful to conduct an audiometric and audiological examination in post-stroke and post-hydrocephalus patients to identify hearing impairment and to define a more accurate diagnosis leading to an appropriate intervention plan [ 12 ]. In addition to the possible link between balance and hearing recovery, early auditory stimulation after a stroke should be recommended to improve neural organization in the recovering brain [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, a need to consider the possibility of “mixed” presentations such as cochlear type HL and CAPD [e.g., Ref. ( 41 )]. Defining normal hearing on the basis of a normal pure tone audiogram is at best insufficient ( 42 ).…”
Section: Apd Definitionmentioning
confidence: 99%
“…With respect to the relationship between vascular health-related factors and central auditory processing, a cross-sectional study in the Framingham cohort reported that a history of heart attack or stroke in women and current smoking in men were related to performance on the Synthetic Sentence Identification test, a test with competing message (Gates et al, 1993), and in a recent case-control study of patients with stroke, cases had significantly higher rates of central auditory processing deficits than controls (Koohi et al, 2017). It has also been reported that individuals with type 2 diabetes had higher speech thresholds in the Hearing in Noise Test (Frisina et al, 2006).…”
Section: Introductionmentioning
confidence: 99%